Pengaruh Digital Marketing, E-WOM, Dan Online Customer Rating Terhadap Keputusan Pembelian Di Culucu Babyshop Nganjuk - Taj, Ziana Walidah; Asiyah, Siti; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to test and analyze the effect of Digital Marketing, E-WOM, and Online Customer Rating on Purchasing Decisions at Culucu Babyshop Nganjuk. The population in this study were Culucu Babyshop consumers whose numbers were unknown. Then from this population a sample of 75 people was taken using the maholtra formula. The variables used in this study are the dependent variable Purchasing Decisions, independent variables Digital Marketing, E-WOM, and Online Customer Rating. The sampling technique in this study used a purposive sampling approach which was assisted by SPSS 25 software in conducting data tests. The results showed that 1) Digital Marketing, E-WOM, and Online Customer Rating simultaneously affect Purchasing Decisions 2) Digital Marketing has no effect on Purchasing Decisions 3) E-WOM has an effect on Purchasing Decisions 4) Online Customer Rating affects Purchasing Decisions. Keywords: Digital Marketing, E-WOM, Online Customer Rating, Purchasing Decision